UTILIZATION OF BLACK SOLDIER FLY (HERMETIA ILLUCENS) AS A PROBLEM SOLVE OF ORGANIC WASTE - Edza Aria Wikurendra (Universitas Fort De Kock, 2020)
Organic waste is a type of waste that has the largest amount in Indonesia. If it is not managed properly, organic waste can cause various problems. To overcome this problem, it is necessary to make an effort to utilize organic waste which also has high economic potential. One solution to this is the use of Black Soldier Fly larvae (Hermetia Illucens) as decomposers of organic matter. The purpose of this study was to analyze the effect of the type of organic waste on the bioconversion of domestic waste using Black Soldier Fly larvae (Hermetia Illucens). This research was done using Black Soldier Fly (Hermetia Illucens) larvae of 7 days old. Two hundred larvae were used for every feeding treatment and placed in a growing cage. The feed types and feeding frequencies were varied. The feed types were three different food waste materials, were mainly composed of cucumber, banana, and canteen’s waste. The larvae were fed with 40 mg of dry weight food waste/larvae.day. The feeding frequency was varied to once per day and once in four day periods. The weight of 10% of larvae per feeding treatment was measured every four days. At the end of the experiment, the residual feed material and characteristics were measured. The level of removal of vegetable waste, fruit waste, and food waste respectively 52 %; 51 %; 55 % on the frequency of feeding once in four days. At the frequency of feeding once a day, the results were 50 %, 62 %; 67%. The C / N ratio of vegetable waste, fruit waste, and food waste residue was 8,8; 10,1; and 11,9 for the frequency of feeding once in four days, and 8,3; 9,2; and 10,6 at the frequency of feeding once a day. The moisture content in the residue of vegetable waste, fruit waste, and food waste were 92,1% respectively; 74,7%; and 77,2% at the frequency of feeding once in four days and 95,2% respectively; 72,6%; and 82,7% at the frequency of feeding once. The pH value of vegetable waste, fruit waste, and food waste is 5,54 respectively; 4,21; and 4,18 for the frequency of feeding once in four days, and 5,47 each; 5,00; and 4,16 for the frequency of feeding once a day. The suggestion for further research is that further research is needed on the effect of the acidity of the food on the mortality rate of the larvae so that the optimum pH for the growth of Black Soldier Fly (Hermetia Illucens) larvae can be found.